Managers' private information, investor underreaction and long-run SEO underperformance - Pawel Bilinski; Norman Strong (The University of Manchester, Manchester Business School, 2009)
Applying the framework of conditional event studies shows that equity issues reveal managers' private information about stock mispricing, which investors only partially discount into stock prices at the seasoned equity offering (SEO) announcement date. Negative abnormal returns occur as prices fully impound the information over a 17-month post-offer period. SEOs exhibit no subsequent underperformance. The study provides a more realistic explanation of SEO underperformance and a framework for testing behavioral explanations of abnormal performance following corporate events.
Keywords: 330; seasoned equity offerings; investor underreaction; manager's private information; Kapitalerhöhung; Anlageverhalten; Wertpapieranalyse; Informationsökonomik